Equimídi@ : uma hipermídia como estratégia pedagógica no ensino de equilíbrio químico - Rocha, Edimarcio Francisco da (2012)
This work presents a research about the teaching of Chemical Equilibrium in High School in which was detected that the teaching-learning process of the contents related to this chemical knowledge has cognitive problems that involve the teachers, the students and the educational material, in this case, the chemistry educational books. Based on these problems, a digital educational material was proposed as a pedagogical strategy for the Chemical Equilibrium teaching. The research was carried out having the quantitative methodology as a presupposition, in which the exploratory approach, the documental search and the case study were present, making as data collection instrument two questionnaires, documents, among them, educational books and articles related to the Chemical Equilibrium teaching and the application of Communication and Information Technologies in education, in addition to a meeting with research subjects who evaluated the educational material. The problems found in the research about the Chemical Equilibrium contents are stated in scientific researches since the last century beginning. These issues are associated mainly to difficulties in abstracting the concepts that the students have. This fact damages the conceptual construction and many times are associated to methodologies which are used by educational material authors and by the teacher who teach this discipline. With the purpose of contributing to the resolution of these learning problems which surround the Chemical Equilibrium teaching, it was proposed one teaching strategy that uses the Communication and Information Technologies based on researches which points that these recourses collaborate with the cognitive development of the individual. So, a material in hypermedia format was developed. This format choice is due to the innumerous possibilities of presenting the contents that this resource permits, providing a faster and more dynamic environment for learning, beyond providing an interactivity between the user and the material, making the individual more participative on his/her learning, what can result in elaboration and understanding of the contents in a more significant way. The material developed, which was denominated as Equimídi@, is constituted by several kinds of media as videos, simulators and texts and is organized by software. Its development has considered technical aspects related to computational interface, for example, interactivity and visualization of information and also pedagogical aspects, as the concepts construction and the content contextualization. To verify the viability of the educational material proposed, the Equimídi@ had passed by an evaluation that was carried out by member who integrate the group of “Programa Institucional de Bolsa de Iniciação à Docência (PIBID)” of the Degree Chemistry Course in UFMT, Cuiabá campus. The results show that the Equimídi@ has relevant educational potential and can result in cognitive development of the user contributing significantly to the Chemical Equilibrium concepts learning.